High abilities in the infanthood: theories, evaluation and main characteristics (Research, Society and Development, 2020)
This article analyzes and discusses high skills or intellectual giftedness, addressing aspects related to theories about the nature of intelligence, the diagnostic evaluation and the main characteristics present in gifted students. For the theoretical framework of the study we are guided by the assumptions defended by Renzulli (2004) and Virgolim (2014), as well as in the current Law of Directives and Bases of Education - LDB 9.394 / 96, among other official documents. The article aims to analyze the theories of intelligence, understand the process of diagnostic evaluation and identify the main characteristics of students with high skills / giftedness in the school context. Regarding the methodology, the study was made possible by a literature review in scientific research databases. The results show that even in the face of legislation, special education still faces many obstacles and it is evident that regular schools are almost always not prepared to receive gifted students. Therefore, at the end of this study, we concluded that continuous education for teachers is essential, especially in the case of working in classes in which there are students with specific learning needs and / or with high skills / giftedness. There needs to be a closer and specific look for students with high skills / giftedness, in order to contemplate them with effective school inclusion, so that these students are an integral part of the teaching-learning process and are not only inserted in the physical space of a classroom.